PENGARUH ARUS KAS BEBAS TERHADAP STRUKTUR MODAL DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERATING (PERIODE PENELITIAN 2012-2016) - ROSYIDA, IRMA (Jurnal Akuntansi AKUNESA, 2017)
This research was conducted to analyze the influence of free cash flow on capital structure with dividend policy as a moderating variable. The sample in this study is 36 companies listed in Indonesia Stock Exchange (IDX) of the years 2012-2016. The analysis technique used is moderated regression analysis (MRA) using the program SPSS 24. This study used the dependent variable capital structure, while the independent variable is free cash flow and dividend policy as moderating variable. The results showed that free cash flow variable simultaneously affect the capital structure. Partially free cash flow negative effect on the capital structure, but the variable dividend policy moderation with a free cash flow does not show significant results.